Early supplementation for cow’s milk allergy prevention in breastfed infants in Poland (ESCAPE-PL): a protocol for randomised controlled trial - Andrea Horvath; Wojciech Feleszko; Agnieszka Bzikowska-Jura; Aleksandra Wesolowska; Agata Stróżyk; Hanna Szajewska; Dominika Ambrożej; Karolina Dumycz (BMJ Open)
Introduction Current recommendations for early introduction of cow’s milk proteins in infants who cannot be breastfed vary and are inconsistent due to a lack of clear evidence. We aim to assess whether early supplementation with various nutritional interventions, including cow’s milk formula (CMF), amino acid formula (AAF), donor human milk (DHM) or high-pressure processed ‘pascalised’ DHM (DHM-P) is effective for the primary prevention of cow’s milk allergy (CMA) in breastfed neonates.Methods and analysis We will perform an open-label randomised, controlled, head-to-head trial with four parallel arms in three Polish study centres (Warsaw). 1000 healthy full-term newborns of mothers eager to exclusively breastfeed will be allocated to receive early supplementation with one of four nutritional interventions: CMF, AAF, DHM or DHM-P. All children will receive 10 mL of each intervention per day for the first 3 days of life; exclusive breastfeeding will be recommended. However, if any supplementation in addition to the breastfeeding is needed, the assigned nutritional intervention will be provided until 4 months of age. The primary outcome is a cumulative incidence of CMA confirmed by open oral food challenge at 4–6 months and 12 months of age. Secondary outcomes include an incidence of sensitisation to cow’s milk protein; a total score in the Cow’s Milk Related Symptom Score; the percentage of children with acquired tolerance to cow’s milk, feeding difficulties and exclusively and predominantly breastfed; an incidence of atopic dermatitis, allergic rhinitis and wheezing; growth; compliance and adverse events. The level of immunomodulatory factors in maternal milk and its nutritional component analysis will also be performed.Ethics and dissemination The ethics committee of the Medical University of Warsaw, Poland, approved this protocol (KB/61/2023). The results of this study will be submitted to a peer-reviewed journal no later than 1 year after data collection. The abstract will be presented at relevant national and international conferences.Trial registration number NCT06652698.